On the competitive ratio of the work function algorithm for the k-server problem - Bartal, Yair; Koutsoupias, Elias (Theoretical computer science, 2004)
The k-server problem is one of the most fundamental online problems. The problem is to schedule k mobile servers to visit a sequence of points in a metric space with minimum total mileage. The k-server conjecture of Manasse, McGeogh, and Sleator states that there exists a k-competitive online algorithm. The conjecture has been open for over 15 years. The top candidate online algorithm for settling this conjecture is the work function algorithm ( WFA) which was shown to have competitive ratio at most 2 k−1. In this paper, we lend support to the conjecture that WFA is in fact k-competitive by proving that it achieves this ratio in several special metric spaces: the line, the star, and all metric spaces with k+2 points.